2021
DOI: 10.25122/jml-2020-0103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice regarding intellectual property rights among dental task force attending private dental colleges in Navi Mumbai: a cross-sectional study

Abstract: Intellectual property rights such as Copyright, Trademark, Patents and Trade secrets etc. help us to gain some protection against certain inventions by acknowledging the founder. In today's industry it is agreed that Intellectual Property Rights has a big role to play. This current study envisages the knowledge, attitude, practice regarding Intellectual Property Rights among dental task force attending private dental colleges.The survey was conducted among students of which were Interns, Post Graduates, facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…In the present study, 41.7% of medical, 40.9% of dental, and 52.2% of nursing professionals did not have any idea regarding protecting their ideas from being copied as compared with another study conducted by Ahmed et al .,[ 18 ] where 47% of participants were not aware of the need to protect the IPRs. A total of 44.3% of medical, 51.5% of dental, and 51.5% of nursing had a knowledge about the importance of IPR in the field of research and development in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 41.7% of medical, 40.9% of dental, and 52.2% of nursing professionals did not have any idea regarding protecting their ideas from being copied as compared with another study conducted by Ahmed et al .,[ 18 ] where 47% of participants were not aware of the need to protect the IPRs. A total of 44.3% of medical, 51.5% of dental, and 51.5% of nursing had a knowledge about the importance of IPR in the field of research and development in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…where knowledge, attitude, and practices regarding IPRs were assessed among the dental task force in Navi Mumbai. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that there were new techniques, formulations and procedures being developed but unfortunately, due to the lack of awareness of IPR among the dentists, these hard-earned findings were at risk of being infringed. The authors recommended that IPR must be a part of the curriculum of dental colleges to improve knowledge of IPR (Kumar et al , 2021). Another study was conducted to identify the level of awareness and mode of acquiring knowledge of IPR among faculty of Library and Information Science (LIS) working in and around Chennai city of India.…”
Section: Literature Reviewmentioning
confidence: 99%